Average Error: 0.0 → 0.0
Time: 8.9s
Precision: 64
$e^{3 \cdot \left(f \cdot x\right) - 2 \cdot f}$
$e^{3 \cdot \left(f \cdot x\right) - 2 \cdot f}$
e^{3 \cdot \left(f \cdot x\right) - 2 \cdot f}
e^{3 \cdot \left(f \cdot x\right) - 2 \cdot f}
double f(double f, double x) {
double r2148988 = 3.0;
double r2148989 = f;
double r2148990 = x;
double r2148991 = r2148989 * r2148990;
double r2148992 = r2148988 * r2148991;
double r2148993 = 2.0;
double r2148994 = r2148993 * r2148989;
double r2148995 = r2148992 - r2148994;
double r2148996 = exp(r2148995);
return r2148996;
}


double f(double f, double x) {
double r2148997 = 3.0;
double r2148998 = f;
double r2148999 = x;
double r2149000 = r2148998 * r2148999;
double r2149001 = r2148997 * r2149000;
double r2149002 = 2.0;
double r2149003 = r2149002 * r2148998;
double r2149004 = r2149001 - r2149003;
double r2149005 = exp(r2149004);
return r2149005;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.0

$e^{3 \cdot \left(f \cdot x\right) - 2 \cdot f}$
2. Final simplification0.0

$\leadsto e^{3 \cdot \left(f \cdot x\right) - 2 \cdot f}$

# Reproduce

herbie shell --seed 1
(FPCore (f x)
:name "exp(3.f*x-2.f)"
:precision binary64
(exp (- (* 3 (* f x)) (* 2 f))))